A Multimodal Discourse Analysis of AI Feature in Samsung Galaxy S24 Ads Video - Camelia, Lia; Rofiq, Zainur (Jurnal Impresi Indonesia, 2025)
This study has analyzed the multimodal construction of artificial intelligence (AI) features in Samsung Galaxy S24 AI Series advertising videos through a social semiotics approach to multimodal discourse analysis. The research focuses on how each AI feature in each segment of the video represents meaning through verbal and visual elements. Verbal elements have been analyzed for Halliday's ideational meaning which focuses on the main character's speech in the video. The visual elements have been analyzed based on Kress and van Leeuwen's visual grammar and how the two elements work together to form a meaning or narrative of advanced technology advertisements such as AI features. The analysis was conducted to explore the narrative and conceptual representations in the video. The results show that the Samsung brand from this video successfully integrates verbal and visual elements to create a narrative of efficiency and convenience, portraying AI technology as an intuitive tool to help users perform daily productivity. The findings contribute to the study of advertising strategies on technology, by highlighting how multimodal approaches influence consumers' perceptions of advanced technology, especially AI technology.